Internal and external load during on-field training drills with an aim of improving the physical performance of players in professional soccer: a retrospective observational study - Ammann, Linda; Chmura, Paweł (Frontiers in Physiology, 2023)
Extensive research has led to evidence-based methodological recommendations for appropriate prescription and implementation of different training drills to improve the physical performance of professional soccer players, while also pointing out limitations of drills. Less is known about the current methods used in an ecological context and the extent to which evidence-based considerations are applied. Knowledge of current practices might also enable to identify pitfalls in successful implementation and/or deficiencies in the communication of scientific knowledge.Thus, the aim of this study was to quantify and compare the load that players experience in an ecological context during drills that are frequently used, and in which there is an intention to improve the players' physical capacities. Therefore, a retrospective observational cohort study was conducted over a 14-month period, analyzing 9 load measures during training drills of 39 players of a team competing in the highest Swiss league. The load experienced by players was statistically significant different between the assessed drill categories for each load measure (all p < .001). This indicates different drills provide different stimuli. HIIT drills proved to be a more powerful tool of getting players to cover distances at high-speed and to spend time at an intensity ≥ 90% HRmax compared to sided games. The sprint distance of players was very low in all sided games and in most cases also in HIIT drills, in the latter the players also hardly performed any deceleration. In small goal-oriented sided games, players covered a greater distance per minute when outside floaters were present. Particularly regarding an improvement of the players' aerobic capacity, the present data emphasize the relevance for coaches to ensure an appropriate exposure. In general, the importance of individual load management in professional soccer is highlighted.